Association Between Birth Weight and Neonatal Respiratory Morbidity: A Cohort Study of Full-Term Infants - Rushan Hassan, Muhammad Maroof Ali, Muhammad Ibrahim, Sumaira Shouket (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Birth weight serves as a vital indicator of neonatal well-being and a key determinant of postnatal adaptation. Both low and high birth weights are associated with increased risk of respiratory complications, even in full-term neonates. Objective: To determine the association between birth weight and neonatal respiratory morbidity among full-term infants. Methodology: This was a prospective cohort study conducted at The Children’s Hospital, Lahore from December 2022 to May 2023. A total of 195 full-term neonates were enrolled using non-probability consecutive sampling. Birth weight was recorded immediately after delivery and categorized as low (<2.5 kg), normal (2.5–4.0 kg), or high (>4.0 kg). All neonates were clinically observed for the first 72 hours for signs of respiratory distress, including tachypnea, grunting, nasal flaring, and retractions. Respiratory morbidity such as transient tachypnea of the newborn (TTN), respiratory distress syndrome (RDS), meconium aspiration syndrome (MAS), and persistent pulmonary hypertension of the newborn (PPHN) was diagnosed using clinical and radiological criteria. Results: Out of 195 neonates, 102 (52.3%) were males and 93 (47.7%) were females, with a mean gestational age of 38.6 ± 1.2 weeks and mean birth weight of 3.1 ± 0.5 kg. Low birth weight was observed in 38 (19.5%) infants, normal weight in 134 (68.7%), and high weight in 23 (11.8%). Respiratory morbidity occurred in 47 (24.1%) neonates. The most common conditions were TTN (10.3%) and RDS (7.2%). A significant association was found between low birth weight and respiratory morbidity (p = 0.02). On multivariate analysis, low birth weight (AOR = 3.21; 95% CI: 1.47–7.03, p = 0.003), cesarean delivery (AOR = 2.14; 95% CI: 1.09–4.23, p = 0.026), and maternal diabetes (AOR = 2.58; 95% CI: 1.01–6.53, p = 0.048) were identified as independent predictors of neonatal respiratory morbidity. Conclusion: It is concluded that low birth weight is significantly associated with increased risk of respiratory morbidity among full-term infants. Cesarean delivery and maternal diabetes further elevate this risk. Keywords: Birth weight, Neonatal respiratory morbidity, Full-term infants, Transient tachypnea of the newborn